Making Sense of Pre-Service English Teachers’ Practicum Experiences: Perspectives on Teacher Learning - Manicio, Maria Teresa L.; Baetiong, Lourdes R. (Philippine Journal of Education Studies (formerly the Education Quarterly), 2024)
This study aimed to explicitly articulate how one learns how to teach English. Guided by sociocultural perspectives on teacher learning (Johnson, 2009), pre- service English teachers’ practicum experiences were examined to gain insights into how they come to know what they know about language teaching. Ten pre- service English teachers recalled and reflected on their practicum experiences through a semi-structured interview and reflection logs. Their teaching practices were also documented through audio/video recorded classroom observations with a follow-up stimulated recall interview. Making sense of learning experiences during practicum revealed that teacher learning was enabled by the guidance of cooperating teachers, the use of symbolic mediation tools for teaching, and challenges in the teaching-learning environment. Recognizing these aspects of teacher learning can support teacher preparation. Teacher education practices should explicitly integrate them into learning experiences that can prepare pre- service English teachers for the complex realities of practice.